KARAKTERISASI TANAMAN JAGUNG UNGU F1 HASIL BERSARI BEBAS JAGUNG MANADO KUNING DENGAN JAGUNG UNGU - Oksandi Darius Tumei; Marjam Toding; Yefta Pamandungan (COCOS, 2018)
ABSTRACT This research aims to study the characteristic of the growth components of purple cornF1resulted from open pollinated between Yellow Manadocornandpurplecorn. Research carried out invillages ofKalasey 2,Mandolangsub-district,Minahasa regency, Province of North Sulawesi during 4 months from June toSeptember 2017.This research was arranged to describe the growthand yield characteristics of purple corn. Seed source used as the treatmentsis:U1 = The seed of purple corn from the fries ear, U2 = The seed of purple corn from the second ear, U3 = The Seed of purple corn from the third ear, U4 = The seed coof purple corn from the fourth ear, U5 = The seed of purple corn from the fifth ear.The results showed that the components of highplant andheight of ear position plant height the highest is obtained from treatment U5 in contrast to the components in the diameter of the stem to be obtained from the U2 treatment being handed out. The coefficiency of variance of the growth and yield components showed low (less than 25%). Keywords : corn characterization, purple corn